Anti-CD19 chimeric antigen receptor T-cell followed by interferon−α therapy induces durable complete remission in donor cell-derived acute lymphoblastic leukemia: A case report - Ni, Jing; Zhou, Junjie; Long, Zhangbiao; Chen, Xin; Chen, Xiaowen; Hong, Jian; Liang, Xinglin; Li, Qingsheng; Xia, Ruixiang; Ge, Jian (Frontiers in Oncology, 2022)
Donor cell-derived leukemia (DCL) is a special type of relapse after allogeneic hematopoietic stem cell transplantation (allo-HSCT). Patient with DCL generally have a poor prognosis due to resistance to conventional chemotherapy. Here, we report a case of donor cell-derived acute lymphoblastic leukemia after umbilical cord blood transplantation. The patient didn’t respond to induction chemotherapy. She then received anti-CD19 CAR-T cell therapy and achieved MRD-negative complete remission (CR). However, MRD levels rose from negative to 0.05% at 5 months after CAR-T cell therapy. Higher MRD levels were significantly associated with an increased risk of leukemia recurrence. Afterward, preemptive interferon-α treatment was administrated to prevent disease recurrence. To date, the patient has maintained MRD-negative CR for 41 months. Our results suggested that anti-CD19 CAR-T cells followed by interferon-α therapy are effective in treating donor cell-derived acute lymphoblastic leukemia. This report provides a novel strategy for the treatment of DCL.